2009
DOI: 10.1159/000204090
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Induces Mouse Embryonic Stem Cell Proliferation Via Ca<sup>2+</sup>/PKC, PI3K/Akt, and MAPKs

Abstract: LA stimulated cell proliferation via Ca2+, PLC/PKC, PI3K/Akt, and p44/42 MAPKs signaling pathways in mouse ES cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 62 publications
0
25
1
1
Order By: Relevance
“…Such difference was due to the presence of linoleic acid in SPE-IV (3.38% of total lipids analyzed) and its absence in aMEM. Notably, from literature, the linoleic acid is known to have a crucial role on membrane fluidity and integrity and was reported to induce mouse embryonic stem cell proliferation (Kim et al, 2009). Interestingly, it was also reported that one of the major and biologically active products of cell peroxidation of n-6 fatty acids, such as linoleic acid, is the aldehyde 4-hydroxynonenal that can trigger the desensitization of PDGFRB to its own agonist together with both a progressive inhibition of its phosphorylation and a partial removal from the cell surface as observed in SPE-IV (Vindis et al, 2007).…”
Section: Lipid Membrane Composition Analysismentioning
confidence: 99%
“…Such difference was due to the presence of linoleic acid in SPE-IV (3.38% of total lipids analyzed) and its absence in aMEM. Notably, from literature, the linoleic acid is known to have a crucial role on membrane fluidity and integrity and was reported to induce mouse embryonic stem cell proliferation (Kim et al, 2009). Interestingly, it was also reported that one of the major and biologically active products of cell peroxidation of n-6 fatty acids, such as linoleic acid, is the aldehyde 4-hydroxynonenal that can trigger the desensitization of PDGFRB to its own agonist together with both a progressive inhibition of its phosphorylation and a partial removal from the cell surface as observed in SPE-IV (Vindis et al, 2007).…”
Section: Lipid Membrane Composition Analysismentioning
confidence: 99%
“…In mouse embryonic stem cells, LA regulates various cell cycle proteins via p44/42 MAPK signaling [18]. Interestingly, unsaturated fatty acids promote the activation of ERK1/2 mainly via FFA1, leading to an anti-lipoapoptotic effect on NIT-1 cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hormones modulate mammary stem cells (LaMarca and Rosen, 2008). Dietary factors stimulate mouse embryonic and hematopoietic stem cell activity (Hinge et al, 2009;Kim et al, 2009). It remains largely unknown, however, whether stem cells and their progeny respond to systemic changes uniformly or more specifically.…”
Section: Introductionmentioning
confidence: 99%